THE POLITICS OF PIETY: Sufism, Power, and Network Formations in Asia-Pacific Islam - Arnel, Iskandar (Asia-Pacific Journal on Religion and Society, 2024)
This article explores the evolving roles of Sufi orders in Asia-Pacific Islam, highlighting their intersections with political authority, religious legitimacy, and digital transformation. Historically, Sufi networks such as the Shattariyya and Qadiriyya–Naqshbandiyya were deeply embedded in the formation of Islamic governance and anti-colonial resistance. Far from being passive or otherworldly, they institutionalized religious authority and shaped Islamic identities across the region. In contemporary contexts, Sufi actors continue to exert influence through translocal networks—particularly the Hadrami diaspora—and by adapting to digital technologies. The rise of virtual zawiyas, social media preaching, and online devotional gatherings reveals a shift in spiritual authority toward more affective, decentralized, and borderless forms. This study argues that Sufism challenges conventional binaries between the spiritual and the political, the local and the global. By positioning themselves as defenders of “moderate Islam” in opposition to Salafi-Wahhabi critiques, many Sufi orders also become key partners in state-led religious governance. Through this lens, Sufism emerges not as a relic of the past, but as a living, networked force shaping the moral and political landscapes of contemporary Islam in the Asia-Pacific.